Investment in selective social programs: a proposed methodological tool for the analysis of programs’ sustainability - Barahona Montero, Manuel Antonio (2014)
This paper proposes a methodology to evaluate sustainability of Selective Social Programs (SSP), based on the relationship between economic growth and human development posed by the United Nations Development Program (UNDP).  For such purposes, the Circle of Sustainability is developed, which is comprised of 12 pillars. Each pillar is evaluated based on its current status and impact.  Combining both results allows to assesses sustainability of these programs and identify areas of focus. Therefore, this methodology helps to better channel available efforts and resources.